2016
DOI: 10.1002/bjs.10107
|View full text |Cite
|
Sign up to set email alerts
|

Balance between von Willebrand factor and ADAMTS13 following major partial hepatectomy

Abstract: There are changes in the balance between VWF and ADAMTS13 levels and activity in patients after both PH and PPPD. Changes in the VWF-ADAMTS13 axis were more pronounced and of longer duration after PH than following PPPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
(89 reference statements)
1
24
0
Order By: Relevance
“…Indeed, both platelet accumulation and liver regeneration were strongly dependent on VWF, although we have not conclusively shown that LSEC (and not plasma or platelet VWF) mediates these processes. We have recently demonstrated that plasma VWF levels increase and levels of the VWF‐cleaving protease ADAMTS13 decrease following partial hepatectomy in humans . Acute VWF release within the liver accompanied by inadequate or delayed removal of reactive VWF molecules by decreased ADAMTS13 levels may explain the transient VWF‐dependent platelet accumulation after partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both platelet accumulation and liver regeneration were strongly dependent on VWF, although we have not conclusively shown that LSEC (and not plasma or platelet VWF) mediates these processes. We have recently demonstrated that plasma VWF levels increase and levels of the VWF‐cleaving protease ADAMTS13 decrease following partial hepatectomy in humans . Acute VWF release within the liver accompanied by inadequate or delayed removal of reactive VWF molecules by decreased ADAMTS13 levels may explain the transient VWF‐dependent platelet accumulation after partial hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma VWF antigen levels were determined by ELISA as described previously (Groeneveld et al , 2016) and pooled normal human plasma was utilized to develop a standard curve. Thiobarbituric acid reactive substances (TBARS) were determined using a commercially available kit (Cayman Chemical, Ann Arbor, MI).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the hypercoagulable state and imbalance between von Willebrand factor (VWF) and ADAMTS13 shortly after a partial hepatectomy has been suggested to contribute to venous and perhaps also portal vein thrombosis. 50 This thrombotic risk may be exacerbated by elevated platelet counts, in particular in the context of the VWF/ADAMTS13 imbalance. Also, elevation of the platelet count in patients with cirrhosis has been shown to elevate the risk of portal vein thrombosis, 51 which may also be linked to the VWF/ADAMTS13 imbalance of cirrhosis.…”
Section: Prospectsmentioning
confidence: 99%